Museums, infinity and the culture of protocols - Morphy, Howard, author.
1 online resource.
Keywords: "Museums, Infinity and the Culture of Protocols enters into a dialogue about museums' responsibility for the curation of its collections into an infinite future, whilst also tackling contentious issues of repatriation and digital access to collections. Bringing into focus a number of key debates centred on ethnographic collections and their relationship with source communities, Morphy considers the value material objects have to different 'local' communities - the museum and the source community - and the value creation processes with which they are entangled. The focus on values and value brings the issue of repatriation and access into a dialogue between the two locals, questioning who has access to collections and whose values are taken into consideration. Placing the museum itself firmly at the centre of the debate, Morphy posits that museums constitute a kind of 'local' embedded in a trajectory of value. Museums, Infinity and the Culture of Protocols challenges aspects of postcolonial theory that position museums in the past by presenting an argument that places relationships with communities as central to the future of museums. This makes the book essential reading for academics and students working in the fields of museum and heritage studies, anthropology, archaeology, indigenous studies, cultural studies and history"-- Provided by publisher.